Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Keaktifan Belajar Siswa di Sekolah Dasar - Titik Setiani; Supangat Supangat; Dyah Pravitasari (Universitas Nurul Huda, 2022)
The activeness of students in teaching and learning activities undergoes various things, including the learning model used by teachers when teaching. The learning model uses the inquiry learning model where its process involves the activeness of students in teaching and learning activities to create critical thinking that is one of logical thinking way focused on decision-making to overcome the problem. In the guided inquiry, the student role is more dominant and active whereas the teacher directs and guides the right way. The problem that will be explained is how it affects the guided inquiry learning model on the activeness of 5th-grade students in SD Negeri Pujorahayu. The research method uses a quasi-experimental design whereas design research uses nonequivalent control group design. This research analyzes 2 classes that are 5th grade of A and B. The result of this research uses a simple linear regression test that the significant value was 0,000 ≤ 0,05 so Ha is accepted and Ho is declined which meant a significant affect between variable of the guided inquiry learning model on the activeness of 5th grade students in SD Negeri Pujorahayu. Explained the percentage of effect of puberty variable (X) on the student learning activeness (Y) is R square of 0,603 meaning that independent effect (guided inquiry learning model) on dependent variable (learning activeness) of 60%. So, guided inquiry learning model effects of 60% on the student learning activeness.